Factors Influencing Small-holder Farmers’ Intention to Adopt Modern Agricultural Technology: A Study on the Non-adopters in Sarawak’s Rural Areas - Dino, Faizul Ayupp; Gadiman, Nur Suriayanti; Isa, Abu Hassan bin Md; Entalai, Michael; Ahmed, Wan Mohd Hamidi Wan (New Advances in Business, Management and Economics Vol. 2, 2025)
Since the introduction of the New Economic Policy (NEP), the agricultural sector has been given attention to ensure that it develops in line with the government's aspiration to ensure a balanced distribution of national income. The agricultural sector remains one of the significant contributors to the country's economy, in which in 2020 it contributes as much as 7.4% to the country's GDP. Despite the government placing a strong emphasis on agricultural development, Malaysia still continues to have a low level of self-sufficiency in its various major food crops. It is widely acknowledged that the use of modern technology can greatly increase the productivity and quality level of agricultural products. Thus, this paper is timely as it investigates the factors that influence the farmers’ intention to adopt modern agricultural technology. By examining the issues from the small-holder food crop farmers’ perspective, a better understanding of the issues can be derived. This can ensure the development of relevant strategies to counter the problems identified. To achieve this objective, the study was conducted within the largest state in Malaysia that is Sarawak, by focusing on the rural small-holder food crop farmers across its central, northern and southern regions. A total of 108 respondents have participated in this researcher-administered survey, who have been chosen based on the purposive sampling method. The data obtained were analysed using the Covariance-based Structural Equation Model (CB-SEM). The findings show that the farmers’ age and voluntariness posed a significant moderating effect on their intention to adopt modern agricultural technology. Moreover, farmers’ gender and past experience have not moderated farmers’ adoption intention. The finding also revealed that social influences did not have a strong influence on farmers' intention to adopt the technology. The implication of these findings shows the importance of increasing farmers’ awareness of the importance of technology in their farming methods, the increased focus on youths to join the agricultural activities and also more training programs for the farmers that are located in the rural areas. Furthermore, government efforts such as skill and awareness training should be conducted in respective villages instead of centrally as most of the farmers are located deeply in rural areas. Government incentives should also be communicated directly to the target group of farmers.